Casting defects analysis in foundry and their remedies: a review - Ali Rizvi , Saadat (Journal of Production Engineering, 2019)
In this current scenario of globalization, foundries play a key role for manufacturing industries as they are the major source of castings. As a key industry a foundry’s performance should be effectively high in terms of production with minimum number of rejections. Castings are the major inputs for most industrial products hence foundry industry is most indispensable. Casting is an integrated process considered as an artwork with experienced professionals for high quality yield, even then in highly controlled environment defects are dominant to take place leading to rejections, contrary to rejections a foundry’s key attempt is to satisfy the demands neglecting quality levels. The challenges of casting defects are to be identified and minimized for effective castings. This study provides an intense knowledge of critical casting defects and their root cause analysis. In this paper efforts are made to achieve technically feasible remedies for minimizing several casting defects and improving the quality of castings which will serve as control measures for quality control professionals with zero defect concepts.